Ghost Stories. Spectral Persistence of the Chilean Detention and Torture Centers [Cuentos de Fantasmas. Persistencia Espectral de Los Centros de Detención y Tortura Chilenos] - Santos-Herceg, J; Pizarro-Cortes, M (Universitat de Valencia, Faculty of Philology, Translation and Communication, 2020)
The detention and torture centres of the Chilean dictatorship have disappeared or are disappearing. The memories of these places also seem to be lost. We will argue here, however, that the physical disappearance of the places does not imply the loss of all traces, since their memory survives through other means, such as oral tradition. We explore, in particular, the possibility that it is the tales of supernatural activity, the so-called "ghost stories", that serve as the public stage for the social memory, allowing it to be summoned. © 2020 Universitat de Valencia, Faculty of Philology, Translation and Communication. All rights reserved.